Інноваційні вокальні технології в освітньому хоровому середовищі - Чурікова-Кушнір Ольга; Churikova-Kushnir Olga (Видавництво «Код», 2025)
Резюме. У статті актуалізовано проблему застосування інноваційних вокальних технологій у процес вокально-хорової підготовки здобувачів закладів вищої освіти. У контексті цифрової освіти розкрито способи модернізації традиційних форм вокально-хорової роботи шляхом поєднання їх з сучасними інструментами: гібридними формами навчання, тренувальними треками, візуалізаторами звуку, інтерактивними освітніми платформами, які сприяють індивідуалізації навчального процесу, покращують точність інтонування, розвивають слуховий самоконтроль, стимулюють самостійність та самоорганізацію здобувачів.

Abstract. The article highlights the issue of applying innovative vocal technologies in the process of vocal and choral training of students in higher education institutions. The purpose of the study is to explore the possibilities of applying innovative vocal technologies and digital teaching aids in the educational choral environment and to analyse their impact on the quality of vocal and choral training of future specialists. To achieve the aim of the study, a set of theoretical (analysis, synthesis, logical generalisation, classification, comparison) and empirical (observation of the educational process in choral groups, questionnaires and interviews with teachers and students) methods were used. The results of the study reveal ways to modernise traditional forms of vocal and choral work by combining them with modern tools: hybrid forms of learning, training tracks, sound visualisations, interactive educational platforms. It has been established that such tools contribute to the individualisation of the learning process, improve intonation accuracy, develop auditory self-control, and stimulate independence and self-organisation among students. It is argued that innovative vocal technologies are not only a technical addition to the educational process, but also a methodological basis for modernising the content of vocal and choral training for students. It is noted that the effectiveness of the innovative approach depends on the combination of technical means with traditional forms of vocal and choral work. At the same time, a number of existing shortcomings are outlined: insufficient digital training of participants in the educational process, fragmentary implementation of the latest technologies, lack of adapted resources, and risks of reducing the emotional and artistic quality of vocal and choral training. The basic principles for introducing innovative vocal technologies into the educational choral environment of higher education students have been developed and substantiated: the principle of pedagogical expediency, the principle of integration, the principle of individualisation, the principle of independence and self-reflection, the principle of active interaction, the principle of gradualism and consistency, and the principle of technological literacy. It has been proven that the set of developed principles forms the methodological basis for the effective integration of innovative vocal technologies into the educational choir environment, which opens up new opportunities for the vocal and choir development of future specialists in the field of musical art. Prospects for further research in this area have been outlined.
Innovative vocal technologies in the educational choral environment
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: вокально-хорова підготовка; інноваційні технології; цифрове хорове середовище; гібридне навчання; тренувальні треки